Uruguay y la guerra en Gaza: entre el realineamiento proisraelí y la ruptura con principios históricos de la política exterior - Hernández Nilson, Diego (El Colegio de México A.C., 2024)
The Uruguayan government under Luis Lacalle Pou reacted to the Hamas attacks on October 7, 2023, by issuing a strong condemnation, in line with Uruguay’s tradition of foreign policy criticizing violence as a tool of international politics and showing solidarity with the State of Israel. However, Uruguay’s subsequent support for Israel’s heightened military response and its evasion of criticizing Israel for the human rights violations that response generated can be seen as departures from some guiding principles that have governed Uruguay’s international stances regarding conflicts of this nature, such as support for peaceful dispute resolution and the defense of human rights. ...